The relationship between transparency and financial performance in Iraqi corporations - Khalid, Talal Mohammed Aljajawy, Anmar Adnan Khudhair, Norlia Mat Norwani, Azam Abdel Hakeem (Opción, 2020)
This study aimed to examine the relationship between transparency and corporate financial performance by using transparency indexes specified in Standard and Poor's model, ownership structure and stakeholder’s rights, financial and non-financial information and board of directions. This study based on a sample of 25 corporations listed on the Iraq stock exchange (ISX). Based on the research results, there is a positive significant relationship between the OWSR and FNF transparency and the financial performance criteria of corporations based on ROA. In conclusion, future studies should be carried out with large sample size and conducted the studies by comprising several other countries.